Título Padrão - Fonteles-Filho, Antônio Adauto; Corrêa Ivo, Carlos Tassito (Arquivos de Ciências do Mar, 2018)
Fishing is a particularly mobile means of harvesting inasmuch as the vessels are able to move a great deal in search of areas with the highest densities of fish, in order to ensure high catching efficiency. In their turn, fish populations follow migratory cycles, mainly correlated with the feeding and reproduction functions, and hence it follows that one of the requirements of a constant checking on them is to determine dispersion patterns so as to be matched with those of fishing distribution.